Symbolic meaning on the poem of I wondered lonely as a Cloud (Daffodils) By William Wordswort's - Irpan Ali Rahman (e-LinguaTera, 2021)
This research is an analysis of a poem written by Willliam Wordswort. The writer analyses the Wordswort's poem titled I Wandered Lonely As a Cloud (Daffodils) to reveal the denotation and connoation as the symbolic meaning. To analyze it the writer uses qualitative-descriptive method to reveal the data. The writer also uses Roland Barthes theory to analyze the symbolic meaning on Wordsworth's poem. Reasearch finding on this analysis is tha the poem of Daffodils mostly uses the naturalistic symbol so that the writer concludes that the poem has full of message of the beauty and powerful of the universe. Wordswort wants us to know his feeling through all these naturalistic symbols.